2019
DOI: 10.1024/0301-1526/a000745
|View full text |Cite
|
Sign up to set email alerts
|

Acute complications in the post-anaesthesia care unit after infrainguinal surgery for lower limb ischaemia – a prospective observational cohort study

Abstract: Abstract. Background: Arterial surgery for lower limb ischaemia is a frequently performed procedure in patients with severe cardio-pulmonary comorbidities, making them high-risk patients for acute postoperative complications with a need for prolonged stay in the post-anaesthesia care unit (PACU). However, detailed information on complications during the PACU stay is limited, hindering mechanism-based interventions for early enhanced recovery. Thus, we aimed to systematically describe acute complications and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Vascular surgery patients were chosen as they are characterised by a high occurrence of comorbidities, especially hypertension, ischemic and incompensated cardiac disease, diabetes, and moderate/severe Chronic Obstructive Pulmonary Disease(COPD) 10 . Interestingly, we found that despite vascular patients having a high proportion of cardiovascular comorbidities, circulatory abnormalities were less common than respiratory abnormalities, in agreement with other studies of vital values of similar patients 19 . We also find that for many of our thresholds, patients do not have long‐lasting sustained deviations as per our thresholds.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Vascular surgery patients were chosen as they are characterised by a high occurrence of comorbidities, especially hypertension, ischemic and incompensated cardiac disease, diabetes, and moderate/severe Chronic Obstructive Pulmonary Disease(COPD) 10 . Interestingly, we found that despite vascular patients having a high proportion of cardiovascular comorbidities, circulatory abnormalities were less common than respiratory abnormalities, in agreement with other studies of vital values of similar patients 19 . We also find that for many of our thresholds, patients do not have long‐lasting sustained deviations as per our thresholds.…”
Section: Discussionsupporting
confidence: 85%
“…10 Interestingly, we found that despite vascular patients having a high proportion of cardiovascular comorbidities, circulatory abnormalities were less common than respiratory abnormalities, in agreement with other studies of vital values of similar patients. 19 We also find that for many of our thresholds, patients do not have long-lasting sustained deviations as per our thresholds. This is due to most events being short-lasting.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations